A 40Wcw Nd:YAG solar laser pumped through a heliostat: A parabolic mirror system - Almeida, Joana (2013)
This research Project (no. PTDC/FIS/103599/2008) was funded by the Science and Technology Foundation of the Portuguese Ministry of Science, Technology and Higher Education (FCT-MCTES). Financial support by the Access to Research Infrastructures Activity in the 7th Framework Programme of the EU (SFERA Grant Agreement no. 228296) is gratefully acknowledged.